Mussel Shell Powder as Bio-adsorbent of Heavy Metals in Water - Darjati Darjati; Marlik Marlik (Health Notions, 2018)
Mussel shell contains chitin and chitosan that can be used as bio-absorbent to reduce heavy metal level in contaminated water. The purpose of this study was to measure the Pb heavy metal level in well water in Keputih residential-formerly a dumping ground-before and after the application of mussel shell powder of 0, 1, 2, and 3 gram by stirring it for 10 and 30 minutes at 60 rpm. The research type was experimental, used One Group PrePost Test Design method. The object was well water which contaminated by leachate at Keputih residential ex dumping ground, Sukolilo Surabaya. The observation showed that the well water in the residential contain heavy metals of 1.049 mg/l. After being given 1, 2 and 3 gram shell powder, it decreases to 58%, 87% and 97%. Based on the statistical test, significant result was obtained at the addition of mussel shell powder of 1 and 3 grams, while addition of 2 grams was not. The conclusion is mussel shell powder can reduce the heavy Pb metal level in the well water in the Sukolilo residential and is advisable that the next researchers continue to check phisical condition of the well water. Keywords: Bio-adsorbent, Heavy metals, Water, Mussel shell powder